Entrepreneurs and Freelancers: Are They Time and Income Multidimensional Poor? The German Case - Joachim Merz; Tim Rathjen (Institute for the Study of Labor (IZA), 2016)
Entrepreneurs and freelancers, the self-employed, commonly are characterized as not only to be relatively rich in income but also as to be rich in time because of their time-sovereignty in principle. Our introducing study scrutinises these results and notions about the well-being situation of self-employed persons not only by asking about traditional single income poverty but also by considering time poverty within the framework of a new interdependent multidimensional (IMD) poverty concept. The German Socio-economic panel with satisfaction data serves as the data base for the population wide evaluation of the substitution/ compensation between genuine, personal leisure time and income. The available detailed Time Use Surveys of 1991/92 and 2001/2 of the Federal Statistics Office provide the data to quantify the multidimensional poverty in all the IMD poverty regimes. Important result: self-employed with regard to single income poverty, single time poverty and interdependent multidimensional time and income poverty in both years are much more affected by time and income poverty than all other active persons defining the working poor. A significant proportion of non-income-poor but time poor of the active population are not able to compensate their time deficit even by an above poverty income. These people are neglected so far within the poverty and well-being discussion, the discussion about the "working poor" and in the discussion about time squeeze and time pressure in general and in particular for the self-employed as entrepreneurs and freelancers.
Keywords: D31; D13; J22; 330; liberal professions (Freie Berufe); entrepreneurs; self-employed; interdependent multidimensional time and income poverty; time and income substitution; extended economic well-being; satisfaction/happiness; CES welfare function estimation; working poor; German Socio-Economic Panel; German Time Use Surveys 1991/02 and 2001/02